ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL SAHAM-SAHAM JAKARTA ISLAMIC INDEX (JII) PADA MASA PANDEMI COVID-19 - Sri Istiyarti Uswatun Chasanah; Syarif Abdullah; Nina Valentika; Usfita Kiftiyani; Agusyarif Rezka Nuha (Program Studi Matematika FMIPA Universitas Pamulang, 2020)
Investment is the wealth of one or more assets in the hope of future benefits. Things to consider in investing are profit and risk. So investors need to diversify their investments, which means investors need to form a portfolio through the selection of several assets so that risk can be minimized without reducing expected profits. The COVID-19 pandemic period had a big impact on the economy, especially for investors in making optimal portfolio formation. This study aims to determine the optimal portfolio formation during the co-19 pandemic using the Single Index Model. The data used are data of consistent shares included in the Jakarta Islamic Index (JII) shares over the past two years. Furthermore, these stocks are chosen which have an average return that is higher than the profits obtained if investors save their money in the bank. The results showed six JII companies included in the candidate for optimal portfolio formation. After the analysis, two shares were produced, namely BRPT with a proportion of 63.8043% and EXCL 36.1957%. The proportion is expected to provide a profit of 1.57% per week and a risk of 6.06% per week. With the proportions obtained, an investment simulation was then carried out during the COVID-19 pandemic. The results of the simulation obtained a gain of 0.0771504% every week. These results are below the risk-free return of assets (SBIS) during the COVID-19-19 pandemic with an average profit of 0.087445% per week. It was concluded that optimal portfolio formation with the Single Index Model did not provide optimal benefits during the COVID-19 pandemic.